Participatory rural appraisal for irrigation management research: lessons from IIMI's experience - Gosselink, P.; Strosser, P. (International Irrigation Management Institute, 1995)
The increasing international awareness about the strengths of participatory approaches and methods for research and development has led international development banks, NGOs, donors and research and training institutes to adopt Participatory Rural Appraisal (PRA) and other participatory approaches to implement new projects and programs. At IIMI, PRA approaches and methods have also'been incorporated in a number of research activities. The present Working Paper explores the opportunities of PRA in irrigation management research through an analysis of selected case studies in which IIMI attempted to practice the PRA approach.